AN INVESTIGATION ON THE PARTIAL REPLACEMENT OF PORTLAND CEMENT WITH KOSOVO FLY ASH IN CEMENT MORTARS - Luga, Erion; Paja, Alban; Atis, Cengiz Duran (MATTER: International Journal of Science and Technology, 2017)
The energy sector is one of the biggest polluters of environment in Kosovo. More than 40 million tons of ash and about 400 hectares of arable land are occupied from the landfill of Kosovo-A and Kosovo-B power plants. On the other hand, the use of fly ashes with proper characteristics, as pozzolanic material in concrete production is a well-known fact. In this context the effect of the partial replacement of Portland cement with Kosovo fly ash in cement pastes and mortars has been investigated. For that purpose, six different series of (0/100, 5/95,10/90,15/85.20/80 and 25/75) fly ash to cement ratios (FA/PC) have been studied. Normal consistency, initial and final setting time of the cement pastes, and water absorption, flexural strength, compressive strength and shrinkage deformation of the mortar specimens were investigated. Test results show that Kosovo fly ash has good parameters that improve the compressive strength of cement mortars and concrete by replacing the Portland cement up to 10%. On the other hand, it increases slightly the water absorption capacity of the mortars. Nevertheless, it can be concluded that the use of Kosovo fly ash in concrete could be a good alternative to be used as a pozzolanic material. Future studies should be focused on the durability effect of Kosovo fly ash on concrete.